2002
DOI: 10.1055/s-2002-35076
|View full text |Cite
|
Sign up to set email alerts
|

Identical Twins are Discordant for Markers of Eccentric Exercise-Induced Muscle Damage

Abstract: This study investigated whether the variability observed in the markers of exercise-induced muscle damage (EIMD) has a genetic etiology. Sixteen pairs of identical twins performed 24 maximal eccentric contractions (24MAX) using the elbow flexors. EIMD indicators were measured pre-24MAX and three days post-24MAX and included: post-exercise force deficit, maximal isometric force (ISO), plasma creatine kinase (CK), myoglobin (Mb), and joint range of motion. Force-time curves were recorded throughout the 24MAX. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…These data suggest there might be a genetic underpinning that causes some individuals to be more susceptible to damage. However, this interpretation is inconsistent with a previous study (Gulbin & Gaffney, 2002) that examined the damage response in 16 pairs of identical twins who performed 24 maximal ECC using the elbow flexors and found the twins did not experience the same amount of muscle damage following an identical exercise bout (Gulbin & Gaffney, 2002). The authors concluded that individual variability following high-force eccentric exercise cannot be attributed to genetic differences.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These data suggest there might be a genetic underpinning that causes some individuals to be more susceptible to damage. However, this interpretation is inconsistent with a previous study (Gulbin & Gaffney, 2002) that examined the damage response in 16 pairs of identical twins who performed 24 maximal ECC using the elbow flexors and found the twins did not experience the same amount of muscle damage following an identical exercise bout (Gulbin & Gaffney, 2002). The authors concluded that individual variability following high-force eccentric exercise cannot be attributed to genetic differences.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 71%
“…Another possible factor that has been attributed to responder status is force application at long muscle lengths. It has been shown that subtle force applications at long muscle lengths can alter a participant's high or low response to the exercise (Gulbin & Gaffney, 2002;Child, Saxton, & Donnelly, 1998;Newham, Jones, Ghosh, & Aurora, 1988). Because this technique (a force-angle curve) was not determined during eccentric muscle contractions in this study, it is possible that "responder" consistency was due to the manner in which participants performed the exercise as well as behavioral factors (i.e., the speed of lowering dumbbell muscle actions during ECC30 and ECC70 or whether the participants had participated in physical activity in the past) may partially account for the consistent response in this study.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Thomis et al (1997) found that the variability in maximal isometric strength of the elbow flexors between 110°and 170°was highly related to genetic factors, and this has also been suggested by Clarkson et al (2005). However, Gulbin and Gaffney (2002), studying pairs of identical twins, concluded that the individual variability in responses to eccentric exercise was not related to genetic heterogeneity. It is likely that differences in training status, level of physical conditioning and musculoskeletal architecture (Fridén and Lieber 2001) were associated with the variability we observed.…”
Section: Discussionmentioning
confidence: 99%
“…30 For this reason, the plasma activity of CK is used as a marker of exercise-induced muscle damage. 31 In some of the cats in the present study, struggling in response to transport in confinement and subsequent handling may have caused plasma CK activity to increase. The skewed distribution of the plasma concentrations of ␣-MSH, ACTH, and cortisol is probably due to the pulsatile release of these hormones.…”
Section: Discussionmentioning
confidence: 68%